A Welfare Economic Interpretation of FRAND - Jens Leth Hougaard; Chiu Yu Ko; Xuyao Zhang (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
Setting an industry-wide standard is crucial for information and communication technologies for interoperability, compatibility and efficiency. To minimize holdup problems, patent holders are often required to ex-ante commit to licensing their technologies under Fair, Reasonable and Non-Discriminatory (FRAND) terms. Yet, there is little consensus, in both courtrooms and industries, on the exact meaning of FRAND. We propose a welfare economic framework that enables a precise distinction: fairness in the distribution of royalty payments among patent users, and reasonableness in setting the size of the compensation to the patent holder, where both the size and the distribution of payments are determined in a non-discriminatory way making sure that similar firms are treated similarly. We illustrate our approach in various classic models from industrial organization, and discuss further potential applications.
Keywords: D63; K2; L3; L44; 330; FRAND-licensing; Fair royalties; Standard setting; Patent; Shapley value